Analysis of student performances in online and face-to-face learning: A case study from a Bosnian public university - Sarah Sarac; Benjamin Durakovic (Heritage and Sustainable Development, 2022)
In the past three years, the COVID-19 became a global health issue and had huge impact on education. This study investigates and compares the student performances after transition from face-to-face learning environment to online learning environments as a result of the spread of the pandemic. Data is collected from a large Bosnian public university and analyzed using statistical tools. In this study student success is defined as passing the course. The results showed that there is significant difference in the performances of students, and it is dependent on learning environment. Particularly, students who attended online classes have significantly higher-grade point averages.